Évaluation de l'impact économique de la COVID-19 en Afrique subsaharienne : perspectives à partir d'un modèle d'équilibre général calculable (EGC) - Calvin Djiofack Zebaze; Hasan Dudu; Albert G. Zeufack (Revue Internationale de Politique de Développement)
This chapter uses a computable general equilibrium model to investigate the likely economic impact of the COVID-19 pandemic in sub-Saharan Africa. We simulate three scenarios: (1) a rapid and effective policy response in sub-Saharan Africa implying that the spread of COVID-19 is contained by early July 2020; (2) a slow and ineffective policy response that prolongs the pandemic through 2021; (3) a worst-case scenario combining scenario 2 and border closures within the region. The decline in regional GDP in 2020 relative to a reference scenario (where the pandemic never occurs) ranges from 5.7% in the relatively optimistic scenario to 7.65 in the pessimistic scenario. The pandemic would lower revenues from taxes and fees while raising spending, leading to a substantial deterioration in the fiscal deficit. Household income would plummet as labour force participation falls. The poor would be disproportionately affected, as many are employed in agriculture and low-end services, where output would fall sharply.